Targets and self-management for the control of blood pressure in stroke and at risk groups (TASMIN-SR): protocol for a randomised controlled trial. - O'Brien, C; Bray, E; Bryan, S; Greenfield, S; Haque, MS; Hobbs, F; Jones, M; Jowett, S; Kaambwa, B; Little, P; Mant, J; Penaloza, C; et al. (BioMed Central, 2013)
BACKGROUND: Self-monitoring of hypertension with self-titration of antihypertensives (self-management) results in lower systolic blood pressure for at least one year. However, few people in high risk groups have been evaluated to date and previous work suggests a smaller effect size in these groups. This trial therefore aims to assess the added value of self-management in high risk groups over and above usual care. METHODS/DESIGN: The targets and self-management for the control of blood pressure in stroke and at risk groups (TASMIN-SR) trial will be a pragmatic primary care based, unblinded, randomised controlled trial of self-management of blood pressure (BP) compared to usual care. Eligible patients will have a history of stroke, coronary heart disease, diabetes or chronic kidney disease and will be recruited from primary care. Participants will be individually randomised to either usual care or self-management. The primary outcome of the trial will be difference in office SBP between intervention and control groups at 12 months adjusted for baseline SBP and covariates. 540 patients will be sufficient to detect a difference in SBP between self-management and usual care of 5 mmHg with 90% power. Secondary outcomes will include self-efficacy, lifestyle behaviours, health-related quality of life and adverse events. An economic analysis will consider both within trial costs and a model extrapolating the results thereafter. A qualitative analysis will gain insights into patients' views, experiences and decision making processes. DISCUSSION: The results of the trial will be directly applicable to primary care in the UK. If successful, self-management of blood pressure in people with stroke and other high risk conditions would be applicable to many hundreds of thousands of individuals in the UK and beyond. TRIAL REGISTRATION: ISRCTN87171227.